Public and Private Returns from Joint Venture Research: An Example from Agriculture - Ulrich, Alvin; Furtan, Hartley; Schmitz, Andrew (Quarterly Journal of Economics, 1986)
Public research institutions are turning increasingly to the private sector for additional financial support. Such a trend, in the short run, lessens the need for public research expenditures, but may, in the long run, prove to be very costly to the economy as a whole. This is because private funding increases the chance that the direction of research will shift so that private benefits are enhanced. Such a shift is especially costly if public research funds are then not forthcoming that would have the potential of producing the maximum level of benefits to the economy as a whole. A case study of Canadian barley research is used to illustrate this problem.